Preserving our heritage perspectives from antiquity to the digital age - Cloonan, Micháele Valerie 1955- (Facet Publishing, 2015)
A collection of key introductory readings of historic preservation literature. Since the essays are presented in an historical timeline, the reader discovers the roots of many current debates. By bringing together material from a variety of sources, this text represents the depth and scope of this intellectually rich field.